Preclinical validation of a novel metastasis-inhibiting Tie1 function-blocking antibody - Singhal, Mahak; Gengenbacher, Nicolas; La Porta, Silvia; Gehrs, Stephanie; Shi, Jingjing; Kamiyama, Miki; Bodenmiller, Diane M; Fischl, Anthony; Schieb, Benjamin; Besemfelder, Eva; Chintharlapalli, Sudhakar; Augustin, Hellmut (EMBO molecular medicine, 2020)
Abstract The angiopoietin (Ang)?Tie pathway has been intensely pursued as candidate second-generation anti-angiogenic target. While much of the translational work has focused on the ligand Ang2, the clinical efficacy of Ang2-targeting drugs is limited and failed to improve patient survival. In turn, the orphan receptor Tie1 remains therapeutically unexplored, although its endothelial-specific genetic deletion has previously been shown to result in a strong reduction in metastatic growth. Here, we report a novel Tie1 function-blocking antibody (AB-Tie1-39), which suppressed postnatal retinal angiogenesis. During primary tumor growth, neoadjuvant administration of AB-Tie1-39 strongly impeded systemic metastasis. Furthermore, the administration of AB-Tie1-39 in a perioperative therapeutic window led to a significant survival advantage as compared to control-IgG-treated mice. Additional in vivo experimental metastasis and in vitro transmigration assays concurrently revealed that AB-Tie1-39 treatment suppressed tumor cell extravasation at secondary sites. Taken together, the data phenocopy previous genetic work in endothelial Tie1 KO mice and thereby validate AB-Tie1-39 as a Tie1 function-blocking antibody. The study establishes Tie1 as a therapeutic target for metastasis in a perioperative or neoadjuvant setting.